The Influence of Competence, Independence, and Audit Risks on the Auditor’s Ability to Detect Corruption with Integrity as a Moderating Variable - Husen Basri; Haryono Umar (Budapest International Research and Critics University, 2021)
This study aims to obtain empirical evidence of the effect of competence, independence, and audit risk on auditors’ ability to detect corruption with integrity as a moderating variable. The population in this study are auditors who work at financial auditor agencies. The sampling was performed using accidental sampling, while the primary data collection used a questionnaire method. The data were then analyzed using structural equation modeling (SEM) partial least square (PLS). The results showed that competence has a positive effect on the auditors' ability to detect corruption, while independence has no positive effect. Furthermore, audit risk has a positive effect on the auditors' ability to detect corruption, and integrity has a positive effect on their ability to detect corruption. Neither does integrity-moderated competencies strengthen the auditor’s ability to detect corruption nor integrity-moderated independence strengthen the auditor’s ability to detect corruption. Finally, integrity-moderated audit risk does not strengthen the auditor’s ability to detect corruption.